Employment, Politics, and Economic Recovery during the Great Depression - Wallis, John Joseph (The Review of Economics and Statistics, 1987)
In earlier studies, economic historians found that political goals, rather than social or humanitarian objectives, motivated much of New Deal spending. Using new information on annual, state level employment for the 1930s, this paper shows that, while politics are still important, responding to the needs of the unemployed was an important determinant of New Deal spending.